A importação ilegal de agrotóxicos pela fronteira de Mato Grosso do Sul com o Paraguai e as implicações para a saúde, o meio ambiente e o desenvolvimento sustentável - JOSÉ RENATO HOJAS LOFRANO (2022)
The present work seeks to study the implications of illegally importing pesticides for health, the environment and sustainable development, a practice that has increased significantly in recent years, especially along the border between Mato Grosso do Sul and Paraguay, despite the existence of a policy government that authorized large amounts of pesticides in the same period. The study involves the process of construction and evolution of human rights, especially those most directly impacted by the phenomenon in question, the vulnerabilities of the border region and the structure of repression and control bodies, analyzing Brazilian and other countries legislation on pesticides. Through empirical research, the qualitative and quantitative analysis of data on seizures of pesticides in a given period of time allowed us to extract valuable information for understanding the problem and proposing measures to combat it. Based on theoretical references, a bibliographic and documental research was carried out, using the inductive approach method and the methods of historical, comparative and statistical procedure, making it possible to start from concrete cases for generalizations. The main reflexes of a penal, civil and administrative nature were studied, but, as it is a complex problem, it was found that the actions of confrontation cannot be restricted to the existing legal instruments, and must involve cultural changes in the relationship between human beings and human beings. its surroundings, including the support of anthropology and the knowledge of indigenous peoples, in order to modify the anthropocentric vision to guarantee a dignified life for all, not only in the present but for future generations.